2018
DOI: 10.1175/jcli-d-17-0352.1
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Ice Sheet–Sea Level Model Incorporating 3D Earth Structure: Variations in Antarctica during the Last Deglacial Retreat

Abstract: A gravitationally self-consistent, global sea level model with 3D viscoelastic Earth structure is interactively coupled to a 3D dynamic ice sheet model, and the coupled model is applied to simulate the evolution of ice cover, sea level changes, and solid Earth deformation over the last deglaciation, from 40 ka to the modern. The results show that incorporating lateral variations in Earth’s structure across Antarctica yields local differences in the modeled ice history and introduces significant uncertainty in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
134
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(143 citation statements)
references
References 64 publications
7
134
2
Order By: Relevance
“…Sometime later the ice shelf made contact with the bathymetric high at the northern end of HIR (Stage 2). Although our data do not explain the cause of regrounding, it was most likely a result of crustal rebound due to GIA following ice unloading (Kingslake et al, ), which is predicted to be large in this area following the LGM (Argus et al, ; Gomez et al, ; Whitehouse et al, ).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Sometime later the ice shelf made contact with the bathymetric high at the northern end of HIR (Stage 2). Although our data do not explain the cause of regrounding, it was most likely a result of crustal rebound due to GIA following ice unloading (Kingslake et al, ), which is predicted to be large in this area following the LGM (Argus et al, ; Gomez et al, ; Whitehouse et al, ).…”
Section: Discussionmentioning
confidence: 60%
“…This gives Hf=trueρi¯ρw()B+wGIAT, where trueρi¯ and ρ w are the depth‐averaged density of the ice and density of sea water. We account for uncertainty in w GIA by considering a range of 5–13 mm/year, covering the present‐day rates from GPS measurements taken on bedrock outcrops around the Weddell Sea sector (4–5 mm/year; Bradley et al, ), and modeled relative sea‐level change for the area over the past 6 kyr (∼12.5 mm/year; Gomez et al, ). Eustatic sea‐level change is at least an order of magnitude slower than this during the period (Lambeck et al, ), so we consider this to be included within the uncertainty range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genuineness of a GIA uplift in ASE was then confirmed by once they constrained spatial wavelength of GIA using forward models. The pronounced GIA-induced uplift is supported by recent GIA models that consider late Holocene IMC which seem to dominate present-day GIA rates in regions that have a thinner lithosphere and a lower mantle viscosity (Barletta et al, 2018;Gomez et al, 2018). The pronounced GIA-induced uplift is supported by recent GIA models that consider late Holocene IMC which seem to dominate present-day GIA rates in regions that have a thinner lithosphere and a lower mantle viscosity (Barletta et al, 2018;Gomez et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
“…Although heavily depending on the regional upper mantle viscosity, Nield et al (2016) have shown that GIA model-predicted rates in this region can reach up to −17 mm/year. A negative GIA-induced signal is also predicted from a coupled model with the 3-D Earth model by Gomez et al (2018) when ice cover changes over the last 3 kyr are considered. A negative GIA-induced signal is also predicted from a coupled model with the 3-D Earth model by Gomez et al (2018) when ice cover changes over the last 3 kyr are considered.…”
Section: Discussionmentioning
confidence: 86%